TARIXIY JARAYONLAR VA IXTIROLARNING HOZIRGI NUTQ TERAPIYASIGA KO‘RSATGAN TA’SIRI (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This work explores the relevance of speech therapy, its role in modern society, its historical development, and current innovative trends. It analyzes the factors contributing to the rise in speech disorders, the importance of speech-therapy intervention, and the impact of anatomical, physiological, and psychological discoveries on the formation of logopaedics. The study highlights the potential of digital tools, mobile applications, artificial intelligence systems, and AR/VR technologies in contemporary speech therapy. The research substantiates the significance of speech therapy in meeting society’s growing needs and improving individual development and quality of life.